Learning Spirituality from Leadership for Ikhlas Work as Spiritual Resources for Engagement and Performance in Public service - Chandra Hosen; Farah Mizafira Wasaraka; Deni Hermana (Global Writing Academica Researching and Publishing, 2026)
This study aims to extend the Job Demands-Resources (JD-R) model by integrating Social Cognitive Theory (SCT) and Conservation of Resources (COR) Theory to examine the influence of Personal Spiritual Leadership (PSL) and Ikhlas Work (sincere/selfless work) as personal resources on work engagement and employee performance in the Indonesian public sector. Employing a multi-paradigmatic approach with an explanatory sequential mixed-methods design, the quantitative phase tested data from 430 Civil State Apparatus (Aparatur Sipil Negara/ASN) using Structural Equation Modelling (SEM-AMOS), followed by a qualitative phase comprising in-depth phenomenological interviews (8–12 informants) and critical observation. The results of the quantitative analysis indicate that PSL exerts a significantly strong positive influence on Ikhlas Work and work engagement. Ikhlas Work was also found to have a direct effect on performance. However, the direct effect of PSL on performance was found to be non-significant, confirming the presence of full mediation by work engagement. Overall, the model successfully explains the variance in performance on the basis of transcendental resource support that sustains engagement. The qualitative findings deepen these results by revealing a methodological-operational gap: macro-level dimensions such as the Qolb Competency in PSL are perceived as a